2022
DOI: 10.3390/ani12192658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Herbal Source of Choline on Diet Digestibility and Palatability, Blood Lipid Profile, Liver Morphology, and Cardiac Function in Dogs

Abstract: We aimed to evaluate the effects of an herbal source of choline on the coefficients of total tract apparent digestibility (CTTAD), diet palatability, fecal characteristics, blood variables, liver morphology, and cardiac function of dogs. Sixteen adult dogs were randomly assigned to two groups (n = 8) which were fed two different diets for 45 days: control, containing 0.28% choline chloride 60, and test, containing 0.14% of an herbal source of choline. Feces were collected between days 39 and 44 to determine nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…By analyzing the pH of the fresh feces of dogs, it was shown that the long-term consumption of either low-or high-energy diets caused fecal acidification, which was related to the metabolites in the feces and the composition of the gut microbiota, in several studies on canine nutrition [50][51][52][76][77][78]. Based on the above, the total SCFAs in the feces were measured in this study and were increased significantly in the Le group, especially for acetic acid and butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the pH of the fresh feces of dogs, it was shown that the long-term consumption of either low-or high-energy diets caused fecal acidification, which was related to the metabolites in the feces and the composition of the gut microbiota, in several studies on canine nutrition [50][51][52][76][77][78]. Based on the above, the total SCFAs in the feces were measured in this study and were increased significantly in the Le group, especially for acetic acid and butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…It is hence of great interest for manufacturers to better understand palatability drivers and adapt their formulations to increase the palatability of veterinary food [34]. Many studies have been recently conducted on new ingredients or formulations for their healthbeneficial effects (such as insect-, plant-, and algal-based meals or byproducts) looking at their impact on pet conditions (weight, digestion, cardiology, immunity) and palatability, offering new opportunities in pet food nutrition and potentially the veterinary pet food range [38][39][40][41].…”
Section: Supporting Health With Veterinary Dietsmentioning
confidence: 99%